Penerapan Ice Breaking Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas X di SMKS Muhammadiyah Bungoro - Andrianisah, Andrianisah; Yunus, Muh; Saripuddin, Saripuddin (CV. Rayyan Dwi Bharata, 2025)
This research aims 1) To increase the learning motivation of class X students through Ice Breaking at SMKS Muhammadiyah Bungoro. 2) To improve the learning outcomes of class X students through Ice Breaking at SMKS Muhammadiyah Bungoro. The research motto used is Classroom Action Research (PTK). The research is carried out in two cycles, each cycle consists of planning, implementation of actions, observation, and reflection. The subject of this study was carried out on class X students at SMKS Muhammadiyah Bungoro which amounted to 25 students. The data collection techniques used in this study were carried out by means of observation, documentation, and written tests. The data analysis technique used in this study is a percentage descriptive analysis in the form of data obtained from 1) the percentage of student learning motivation and 2) the improvement of learning outcomes obtained from the average score of pretest and posttest student learning outcomes before and after the implementation of Ice Breaking. The results of this study show that 1) Students' learning motivation before and after ice breaking has increased. 2) The learning outcomes of students before and after the ice breaking were increased. This can be seen in the learning process showing greater student learning motivation in learning activities which is shown by the behavior of actively answering questions, the amount of interest in attending lessons and great attention to project subjects. Student learning outcomes have increased, namely 50.08 in the initial condition, 66.60 in Cycle I, and 77.80 in Cycle. In addition, the number of students who meet the KKTP has also increased, namely 10 students in the initial condition, 12 students in Cycle I, and 20 students in Cycle II.